Lipid Peroxidation and Antioxidant Activities of the Aqueous Rhizome Extract of Rheum officinale Baillon - Eugene Chang; Choon Young Kim (Journal of Food Quality)
Generation of reactive oxygen species (ROS) is associated with dysregulation of antioxidant defense mechanisms and incidence of human diseases. The specific aim of this study was to investigate the lipid oxidation and antioxidant activity of aqueous extract of Rheum officinale Baillon rhizome in order to evaluate its potential as a future novel natural antioxidant resource and a functional ingredient in food and pharmaceutical formations. Total phenolic and flavonoid contents of Rheum rhizome extract were dose dependently increased. Consistent with this, radical scavenging activities of Rheum rhizome extract as determined by 2,2-diphenyl-1-picrylhydrazyl assay and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activity were significantly elevated as the concentration increased. In addition, the treatment of aqueous Rheum rhizome extract significantly increased ferric reducing and copper chelating activities. According to results of thiobarbituric acid reactive substance analysis, Rheum rhizome extract significantly delayed lipid oxidation. Preincubation with Rheum rhizome extract significantly inhibited tert-butyl hydroperoxide- (t-BHP-) induced ROS generation. Moreover, superoxide anion production was significantly lower in Rheum rhizome extract-treated RAW264.7 macrophage cells than t-BHP-incubated cells (p<0.05). These findings suggest that Rheum officinale Baillon rhizome extract has a potential as an excellent natural antioxidant agent.